Analysis of the Replacement Crew Mechanism on the Performance of the Crewing Department at PT Jasindo Duta Segara - Titis Ari Wibowo; April Gunawan Malau; Damoyanto Purba; Ardy Nugraha (Dinasti International Journal of Management Science, 2022)
Era of globalization, sea transportation gave rise to crewing companies to look for ship crew resources to perform crew replacements order to get quality crews to work on ships. To expedite these activities, the company has taken every step to ensure replacement crew activities run well and optimally. This study uses descriptive quantitative methods, with data collection using questionnaires, observations, literature studies, and documentation so the data can be processed using quantitative descriptive data analysis. The results showed the cause of declining crewing department performance was due the non-optimal replacement of ship's crew, and how to deal with it was evaluated for each implementation. Crew changes must be made according to the position and experience of the crew itself.